Economic Development and Energy Transition Readiness Using Spline Approach: Evidence from Asia Region - Muhammad Syukri; Aditya Idris (CV. Sakura Digital Nusantara, 2026)
Purpose – This study examines the impact of energy transition readiness on economic development in Asian countries by analyzing five dimensions: regulation & political commitment, infrastructure, education & human capital, innovation, and finance & investments. Design/Methodology/Approach – A spline regression approach was employed to capture the non-linear relationship between energy transition readiness and GDP per capita. Data from Asian countries were analyzed to identify threshold effects across readiness dimensions. Findings – The results show heterogeneous non-linear effects of energy transition readiness on GDP. Regulation & political commitment and infrastructure have consistently significant impacts, while innovation and finance & investments become significant only after certain readiness thresholds. Education & human capital does not show a significant effect. Originality/Value – This study extends the literature by demonstrating that the economic benefits of energy transition readiness are non-linear and vary across development stages. The findings provide policy guidance for Asian countries to adopt targeted, stage-specific strategies that strengthen energy transition readiness and promote sustainable economic development.